That’s a Wrap! Molecular Drivers Governing Neuronal Nogo Receptor-Dependent Myelin Plasticity and Integrity - Petratos, Steven; Theotokis, Paschalis; Kim, Min Jung; Azari, Michael F.; Lee, Jae Young (Frontiers in Cellular Neuroscience, 2020)
Myelin is a dynamic membrane that is important for coordinating the fast propagation of action potentials along small or large caliber axons (0.1 - 10 μm) some of which extend the entire length of the spinal cord. Due to the heterogeneity of electrical and energy demands of the variable neuronal populations, the axo-myelinic and axo-glial interactions that regulate the biophysical properties of myelinated axons also vary in terms of molecular interactions at the membrane interfaces. An important topic of debate in neuroscience is how myelin is maintained and modified under neuronal control and how disruption of this control (due to disease or injury) can initiate and/or propagate neurodegeneration. One of the key molecular signaling cascades that has been investigated in the context of neural injury over the past two decades involves the myelin-associated inhibitory factors (MAIFs) that interact with Nogo receptor 1 (NgR1). Chief among the MAIF superfamily of molecules is a reticulon family protein, Nogo-A, that is established as a potent inhibitor of neurite sprouting and axon regeneration. However, an understated role for NgR1 is its ability to control axo-myelin interactions and Nogo-A specific ligand binding. These interactions may occur at axo-dendritic and axo-glial synapses regulating their functional and dynamic membrane domains. The current review provides a comprehensive analysis of how neuronal NgR1 can regulate myelin thickness and plasticity under normal and disease conditions. Specifically, we discuss how NgR1 plays an important role in regulating paranodal and juxtaparanodal domains through specific signal transduction cascades that are important for microdomain molecular architecture and action potential propagation. Potential therapeutics designed to target NgR1-dependent signaling during disease are being developed in animal models since interference with the involvement of the receptor may facilitate neurological recovery. Hence, the regulatory role played by NgR1 in the axo-myelinic interface is an important research field of clinical significance that requires comprehensive investigation.